Madan Mohan Malaviya and the Indian freedom movement - Misra, J. P. (OUP, 2016)
At the time when the national movement was still in its early stages, Madan Mohan Malaviya emerged as an enigmatic but commanding figure in the political landscape of India. This work reconstructs Malaviya’s ideal of nationalism, which was composite, constructive and creative and offers a fresh perspective on an important period of modern India’s political history. Utilizing new and authentic source material, this book traces Malaviya’s role in the freedom struggle, the people who supported him, his relations with other established political leaders of the country within and outside of the Congress party and how he saw his own actions and role in public life. Taking Malaviya as a particular example of subcontinental leadership, Jagannath Prasad Misra studies the method and manner of Malaviya’s nationalist propaganda. He shows that rather than being a restraining influence, Malaviya’s faith in constitutional politics and educational advancement laid a solid foundation for the uplift of the nation.